Enhanced solubility and stability of antioxidants from Mangifera pajang in natural deep eutectic solvent of choline chloride/ascorbic acid - Ling, Jordy Kim Ung (Curtin University, 2020)
This research work prepared a choline chloride/ascorbic acid natural deep eutectic solvent (CHCL/AA NADES) to enhance the solubility and stability of antioxidants extracts from the fruit wastes of Mangifera pajang. CHCL/AA NADES enhanced the solubility of antioxidant extracts by 11% as compared to water. Moreover, CHCL/AA NADES stabilized the antioxidant extracts under high temperature and pH by extending its half-life duration, determined by first-order kinetic model and a new proposed multi-term degradation model.